Pengembangan Media Pembelajaran Berbasis Video Animasi Pada Simulasi Praktikum Operational Amplifier (Op-Amp) Kompetensi Keahlian Elektronika Industri Kelas XI SMKN 29 Jakarta - Pratama, Febriyanto; Sukardjo, Moch; Oktaviani, Vina (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2023)
This research aims to develop animated video-based learning media in the Operational Amplifier (Op-Amp) practicum simulation, the competence of Industrial Electronics class XI expertise at SMKN 29 Jakarta, as well as to test the feasibility level of learning media based on assessments by material experts, linguists, instructional design experts, and media experts. This research is a development research that refers to the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) research model. The product resulting from this study is in the form of an animated video-based learning video on the Operational Amplifier (Op-Amp) practicum material for the application of electronic circuits. Based on the results of feasibility tests conducted by material experts obtained a percentage of 82.53%, linguists obtained a percentage of 86.11%, instructional design experts 96.35%, and media experts obtained a percentage of 91.07%, and user test results obtained a percentage of 96.24% for individual tests and 95% for small group tests. The results of this study show that animated video-based learning media on Operational Amplifier (Op-Amp) practicum material, especially in the subject of Application of Electronic Circuits, is included in the category of very valid/very feasible.